Pemetaan Sebaran Pasir Besi di Pantai Sunur, Kec. Pariaman Selatan, Kota Pariaman, Sumatera Barat. - Rafky Maulana; Adree Octova (Jurusan Teknik Pertambangan FT UNP, 2023)
South Pariaman Subdistrict, Pariaman City has abundant iron sand mineral resources. However, the use of iron sand in the area is still less than optimal because the local government and local communities do not have data on iron sand exploration in the area. Mineral resources are mineral deposits that are expected to be utilized in real terms. Mining resources with certain geological beliefs can change into reserves after a mine feasibility assessment is carried out and meets the criteria. The purpose of this study is to determine the distribution of iron sand in the study area, the value of the percentage of magnetism, the percentage of magnetic mineral value. There are 21 borehole points with a depth of 0-2 m. From this research, several results were obtained, including from the borehole lithology process, it was known that the material contained varied from medium sand with a size of 0.25-0.55mm and fine sand with a size of 0.125-0.25mm. After preparing the sample, the largest percentage of magnetism (MD) was obtained at point 17 of 26.36% and the smallest percentage at point 20 of 6.04%. The largest percentage of magnetic minerals (MM) at point 17 was obtained at point 17 at 30.85% and the smallest percentage at point 20 was 7.61%. From the magnetic percentage value and the percentage of magnetic mineral value, a magnetic percentage value distribution map and magnetic mineral distribution map were made using the Inverse Distance Weighted (IDW) method which shows that the value of the distribution of iron sand in the part leading to the ocean is greater than in other areas.